A photocatalytic fenton cooperated silicon carbide electrochemical mechanical polishing pad and a preparation method thereof

CN122914034APending Publication Date: 2026-10-16XINGHUA TSINGKE (TIANJIN) ELECTRONIC MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611349694.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-02
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

然而,现有ECMP技术在实际应用中仍存在芬顿反应催化剂难以控制、Fe3+/Fe2+循环速率较慢、光催化效率受限以及电化学氧化不均匀等问题

Benefits of technology

一、本发明通过螯合剂将Fe2+固定于聚氨酯多孔层的孔壁上,使Fe2+能够在抛光界面缓慢、持续且较为均匀地释放,避免将Fe2+直接加入抛光液时容易出现的氧化失活、沉淀以及H2O2快速损耗等问题,提高芬顿反应过程的稳定性和可控性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122914034A_ABST
    Figure CN122914034A_ABST
Patent Text Reader

Abstract

The application provides a photocatalytic Fenton synergic silicon carbide electrochemical mechanical polishing pad and a preparation method. The polishing pad comprises a plastic sheet and a polyurethane porous layer attached to the plastic sheet, and the polyurethane porous layer is provided with a photocatalyst, a divalent iron ion chelate and composite magnetic particles. In the preparation, a polyurethane resin containing a chelating agent, a photocatalyst and composite magnetic particles is prepared first, and then is coated, solidified, washed and dried to form a polyurethane porous layer, and then is immersed in a ferrous salt aqueous solution to make the divalent iron ions chelate with the chelating agent, and then is attached to the plastic sheet and is polished and cut to obtain the polishing pad. In the polishing process, the photo-generated electrons promote the reduction of Fe 3+ to Fe 2+ , accelerate the Fe 3+ / Fe 2+ cycle, and the composite magnetic particles adjust the modulus and hardness of the polishing pad under the action of an external magnetic field, so that the material removal rate, surface quality and continuous polishing stability of the silicon carbide wafer are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of ultra-precision machining technology for silicon carbide wafers, and in particular to a photocatalytic Fenton-synergistic silicon carbide electrochemical mechanical polishing pad and its preparation method. Background Technology

[0002] Single-crystal silicon carbide (SiC) is a typical representative of third-generation semiconductor materials. Compared with first-generation semiconductor materials such as silicon and germanium, and second-generation semiconductor materials such as gallium arsenide and indium phosphide, SiC has a wider bandgap, higher thermal conductivity, higher critical breakdown electric field strength, and greater electron saturation drift velocity. It is particularly suitable for fabricating high-voltage, high-frequency, and high-power electronic devices, and has important application prospects in fields such as 5G communication, new energy vehicles, high-speed rail transportation, smart grids, and aerospace.

[0003] While SiC materials possess excellent properties, they also present significant challenges in processing and manufacturing. SiC has a Mohs hardness of 9.2–9.6, second only to diamond, and exhibits high chemical inertness and significant brittleness. In semiconductor device manufacturing, the surface quality of SiC wafers directly affects device performance and reliability. Typically, a SiC substrate surface with a roughness Ra of less than 0.3 nm, free of significant defects and subsurface damage, is required to meet the requirements of subsequent epitaxial layer growth. Therefore, ultra-precision polishing of SiC wafers is a crucial processing step for its large-scale applications.

[0004] Electrochemical mechanical polishing (ECMP) is currently one of the effective methods for processing SiC. Its principle involves using the SiC wafer as the anode, electrochemically anolyzing it to generate a relatively low-hardness SiO2 oxide layer on the SiC surface, and then removing this oxide layer through the mechanical action of an abrasive or polishing pad, thus achieving surface planarization of the SiC wafer. However, existing ECMP technology still faces challenges in practical applications, such as difficulty in controlling the Fenton reaction catalyst and Fe... 3+ / Fe 2+ Problems include slow cycle rate, limited photocatalytic efficiency, and uneven electrochemical oxidation.

[0005] In the Fenton reaction, Fe 2+ The reaction with H2O2 can generate highly oxidizing hydroxyl radicals, thereby improving the oxidation efficiency of the SiC surface, but the reaction with Fe... 2+ After directly adding the polishing slurry, Fe 2+ It is easily oxidized to Fe 3+ It may also react with abrasives such as silica sol to produce precipitates; Fe 2+The decomposition effect on H2O2 is strong, easily causing rapid H2O2 loss. Furthermore, the Fenton reaction occurs throughout the polishing solution, resulting in a relatively small number of hydroxyl radicals actually acting on the polishing interface, and their distribution is not uniform. Meanwhile, Fe... 2+ It reacts with H2O2 to form Fe 3+ And Fe 3+ Reduced to Fe 2+ The relatively slow rate of the reaction leads to a gradual decrease in the efficiency of the Fenton reaction, thus limiting the utilization rate of H2O2.

[0006] Photocatalytic assisted polishing mainly utilizes ultraviolet light to excite photocatalysts to generate photogenerated electrons and holes, and further generate hydroxyl radicals. However, photogenerated electrons and holes are prone to recombination, resulting in low quantum efficiency. When the photocatalyst is dispersed in the polishing slurry in a free form, it is also easy for the photocatalyst to leave the polishing interface with the flow of the polishing slurry, resulting in insufficient effective hydroxyl radical concentration reaching the SiC surface, making it difficult to form a continuous and stable catalytic effect at the polishing interface.

[0007] During electrochemical mechanical polishing (EMF), the uneven current density distribution on the SiC wafer surface leads to preferential oxidation at scratches and defects, resulting in localized over-etching and affecting wafer surface quality. The common cause of these problems lies in the Fe in the Fenton reaction. 2+ Catalysts and photocatalysts typically exist in free form in polishing slurries, making catalyst distribution difficult to control and resulting in insufficient concentration at the reaction interface. (Fe...) 3+ / Fe 2+ The cycle lacks an effective electron donor, and electrochemical oxidation and chemical oxidation occur separately, failing to achieve sufficient synergy.

[0008] In the prior art, CN121733450A discloses a catalytic polishing pad for fine polishing of silicon carbide substrates and its preparation method, which achieves Fe... 2+ The controlled release of Fe can improve 2+ The direct addition of polishing slurry presents problems such as instability, easy precipitation, and rapid loss of H2O2. However, the efficiency of the Fenton reaction will gradually decrease as the polishing time increases, making it difficult to meet the requirements for long-term stable polishing.

[0009] CN116214359B discloses a method for polishing single-crystal silicon carbide with photoelectrocatalytic enhancement of solidified abrasive, which can concentrate force, heat, light, electricity and chemical reactions in the polishing contact area. However, this method relies on the piezoelectric material to emit light under stress, and the light emission intensity and duration are limited by mechanical stress conditions, making it difficult to flexibly adjust the photocatalytic reaction rate according to the polishing process requirements.

[0010] CN115386298A discloses a silicon carbide chemical mechanical polishing slurry based on photocatalysis. The ester modification improves the dispersibility and permeability of the photocatalyst in the polishing slurry. However, the photocatalyst is still dispersed in the polishing slurry in a free form. In the actual polishing process, it is easy to leave the polishing interface with the flow of the polishing slurry, resulting in insufficient concentration of effective hydroxyl radicals reaching the SiC surface.

[0011] Furthermore, in existing piezoelectric-assisted Fenton reaction-based chemical mechanical polishing schemes, the metal ions and photocatalysts in the Fenton system still mainly exist in free form in the polishing solution, resulting in uneven distribution and difficulty in controlling the reaction process; due to the photogenerated electrons generated by the photocatalyst and Fe... 3+ Spatially separated, with long electron transport paths, it is difficult to fully utilize photogenerated electrons to promote Fe... 3+ / Fe 2+ The synergistic effect of cycles.

[0012] To this end, a photocatalytic Fenton-synergistic silicon carbide electrochemical mechanical polishing pad and its preparation method are proposed. Summary of the Invention

[0013] The technical solution of the present invention is implemented as follows: a photocatalytic Fenton synergistic silicon carbide electrochemical mechanical polishing pad, the polishing pad comprising a plastic sheet and a polyurethane porous layer adhered to the plastic sheet, the polyurethane porous layer being a porous damping cloth structure comprising a polymer matrix, a photocatalyst, a ferrous ion chelate and composite magnetic particles.

[0014] The polymer matrix is ​​composed of polyurethane resin containing chelating groups and has a porous structure; the photocatalyst is dispersed in the polymer matrix or supported on the pore walls of the polymer matrix; ferrous ions are fixed on the pore walls of the polymer matrix through chelation and form ferrous ion chelates; the composite magnetic particles are dispersed in the polymer matrix.

[0015] Furthermore, the photocatalyst is selected from one or more of TiO2, CeO2-TiO2 heterostructure, Ag@AgCl and g-C3N4, and the particle size of the photocatalyst is 10-100 nm.

[0016] Furthermore, the photocatalyst nanoparticles are uniformly dispersed on the pore wall surface of the polymer matrix and spatially adjacent to the ferrous ion chelates fixed on the pore walls, enabling the photogenerated electrons generated by the photocatalyst after ultraviolet light excitation to transfer to the Fe... 3+ Promote Fe 3+ Reduced to Fe 2+ .

[0017] Furthermore, the chelating group is introduced by a chelating agent selected from one or more of N-hydroxyethylethylenediaminetriacetic acid, ethylenediaminetetraacetic acid, and diethylenetriaminepentaacetic acid.

[0018] Furthermore, the composite magnetic particles are CIP@Fe3O4 composite magnetic particles or Fe3O4@SiO2 composite magnetic particles.

[0019] Furthermore, the CIP@Fe3O4 composite magnetic particles are core-shell structured particles with carbonyl iron powder as the core and iron(III) oxide as the shell. The nano-sized Fe3O4 on the surface of the CIP@Fe3O4 composite magnetic particles can participate in the auxiliary catalysis of the Fenton reaction and give the polishing pad magnetic responsiveness; when an external magnetic field is applied during the polishing process, the modulus and hardness of the polishing pad can be adjusted by adjusting the magnetic field strength.

[0020] This invention also provides a method for preparing the above-mentioned photocatalytic Fenton-synergistic silicon carbide electrochemical mechanical polishing pad, comprising the following steps: S1, to prepare a polyurethane resin containing a photocatalyst, a chelating agent and composite magnetic particles; 1,4-Butanediol, polybutylene adipate diol, N-hydroxyethyl ethylenediamine triacetic acid, diphenylmethane-4,4′-diisocyanate, organosilicon prepolymer, photocatalyst nanoparticles, and CIP@Fe3O4 composite magnetic particles were mixed and reacted in N,N-dimethylformamide to obtain an organosilicon-modified solvent-based polyurethane resin containing chelating agents, photocatalysts, and composite magnetic particles.

[0021] By mass percentage, the 1,4-butanediol is 0.5%–3%, the polybutylene adipate diol is 20%–30%, the N-hydroxyethyl ethylenediamine triacetic acid is 0.5%–5%, the diphenylmethane-4,4′-diisocyanate is 5%–15%, the N,N-dimethylformamide is 60%–74%, the organosilicon prepolymer is 5%–15%, the photocatalyst nanoparticles are 1%–10%, and the CIP@Fe3O4 composite magnetic particles are 5%–20%; the number average molecular weight of the polybutylene adipate diol is 1800–3000.

[0022] Specifically, the 1,4-butanediol, polybutylene adipate diol, and a portion of N,N-dimethylformamide are mixed and stirred, heated to 75–85°C, and diphenylmethane-4,4′-diisocyanate and a portion of N,N-dimethylformamide are added to carry out a polymerization reaction. As the viscosity of the reaction system increases, the remaining N,N-dimethylformamide is added, and the reaction is carried out for 3–7 h, followed by cooling to 50–60°C. The N-hydroxyethyl ethylenediamine triacetic acid, photocatalyst nanoparticles, and CIP@Fe3O4 composite magnetic particles are dispersed in N,N-dimethylformamide, ultrasonically dispersed for 30–60 min, and then slowly added to the reaction system. The reaction is continued for 2–5 h, and then the temperature is lowered to 30–40°C to obtain the organosilicon-modified solvent-based polyurethane resin.

[0023] S2, prepare a porous polyurethane layer; The silicone-modified solvent-based polyurethane resin obtained in step S1 is mixed with N,N-dimethylformamide at a mass ratio of 60-70:30-40 to prepare a coating slurry. The coating slurry is applied to a plastic substrate and then immersed in a coagulation bath prepared with N,N-dimethylformamide and pure water at a mass ratio of 10-30:70-90 to solidify, thereby obtaining a polyurethane porous layer. The polyurethane porous layer is then washed with pure water and dried.

[0024] S3, which fixes ferrous ions; The polyurethane porous layer obtained in step S2 is immersed in a ferrous salt aqueous solution with a mass concentration of 0.1% to 10%, so that the chelating agent in the polyurethane resin reacts with the ferrous ions to form ferrous ion chelates. After drying, a catalytic polyurethane porous layer containing a photocatalyst, composite magnetic particles and ferrous ion chelates is obtained.

[0025] The ferrous salt is selected from one or more of ferrous sulfate, ferrous chloride, and ferrous nitrate.

[0026] S4, perform post-processing; The catalytic polyurethane porous layer obtained in step S3 is bonded to a plastic sheet, and then polished and cut to obtain the photocatalytic Fenton synergistic silicon carbide electrochemical mechanical polishing pad.

[0027] The polishing pad is attached to the polishing disc of an electrochemical mechanical polishing (EMF) device during use. A polishing solution containing 3–7.5 wt% H₂O₂ and an electrolyte is used. The SiC wafer is connected as the anode to the positive terminal of the power supply, and the polishing disc is connected as the cathode to the negative terminal. During polishing, a wavelength of 365 nm and a light intensity of 50–100 mW / cm² are used. 2 The surface of the polishing pad is irradiated with ultraviolet light, an external voltage of 5–25 V and an external magnetic field of 0–500 mT are applied, the polishing pressure is 15–50 kPa, and the polishing disc speed is 40–80 rpm.

[0028] During the polishing process, ultraviolet light excites the photocatalyst in the polishing pad to generate photogenerated electrons and holes. The holes react with water or hydroxide ions to generate hydroxyl radicals; Fe is chelated and fixed in the polishing pad. 2+ It is slowly released in the polishing solution environment and reacts with H2O2 to generate hydroxyl radicals; the photogenerated electrons generated by the photocatalyst will ignite the Fe formed in the Fenton reaction. 3+ Reduced to Fe 2 + Promote Fe 2+ Regeneration, accelerating Fe 3+ / Fe 2+ The process involves a cycle where composite magnetic particles adjust the modulus and hardness of the polishing pad under the influence of an external magnetic field; an external electric field causes anodic oxidation of the SiC surface to form a SiO2 oxide layer, which is then removed by mechanical action, thus forming a continuous polishing process of oxidation, removal, and re-oxidation.

[0029] The embodiments of the present invention have the following advantages due to the adoption of the above technical solutions: I. This invention uses a chelating agent to bind Fe 2+ Fixed to the pore walls of the polyurethane porous layer, so that Fe 2+ It can release Fe slowly, continuously, and relatively evenly at the polishing interface, avoiding the release of Fe. 2+ This addresses the problems that easily arise when directly adding polishing slurry, such as oxidation deactivation, precipitation, and rapid H2O2 loss, thereby improving the stability and controllability of the Fenton reaction process.

[0030] II. This invention utilizes photogenerated electrons produced by a photocatalyst to convert the Fe formed during the Fenton reaction. 3+ Reduced to Fe 2 + Accelerate Fe 3+ / Fe 2+ Circulation, improving Fe in the traditional Fenton reaction 3+ To Fe 2+ The slow conversion rate makes Fe 2+ It can continuously regenerate, improving the generation rate and utilization efficiency of hydroxyl radicals.

[0031] III. This invention combines photocatalyst and Fe 2+ The chelates are jointly immobilized in the polishing pad, and both are distributed adjacently on the pore walls of the polyurethane porous layer, facilitating the generation of photogenerated electrons and Fe. 3+ The reduction occurs in the same micro-region, shortening the electron transfer path and enabling in-situ synergy between photocatalytic reaction and Fenton reaction at the polishing interface.

[0032] Fourth, this invention incorporates CIP@Fe3O4 composite magnetic particles into a polymer matrix, giving the polishing pad magnetic responsiveness. Under the influence of an external magnetic field, the modulus and hardness of the polishing pad can be adjusted, thereby adjusting the contact pressure between the polishing pad and the SiC wafer according to the polishing conditions. This is beneficial for balancing material removal rate and surface processing quality.

[0033] V. This invention enables the hydroxyl radicals generated by photocatalysis and Fenton reaction to work synergistically with electrochemical anodizing on the same polishing interface, thereby improving the oxidation efficiency of the SiC surface and removing the formed oxide layer in a timely manner through mechanical action, thus improving the material removal rate of the SiC wafer; according to the disclosure, the material removal rate can reach 2 to 5 μm / h.

[0034] VI. This invention utilizes photocatalysts and Fe... 2+ Chelates and composite magnetic particles are concentrated in the polishing pad, so that the catalytic reaction mainly occurs in the polishing contact area. The modulus and hardness of the polishing pad are adjusted by the magnetic field, which helps to improve the pressure distribution and oxidation uniformity of the polishing interface, reduce local over-corrosion, and the surface roughness Ra after polishing can reach 0.2 to 0.5 nm.

[0035] VII. This invention continuously promotes Fe through photogenerated electrons. 3+ Reduced to Fe 2+ This allows the Fenton reaction to maintain high efficiency during long-term polishing; during continuous 40-hour polishing, the material removal rate remains stable, and the MRR retention rate reaches over 97%, which can improve the problem of polishing efficiency decay that occurs with the extension of the use time of existing Fenton catalytic polishing pads.

[0036] 8. This invention combines photocatalyst and Fe 2+ The catalytic components are fixed in the polishing pad, and the polishing solution can be mainly composed of H2O2 and electrolyte. There is no need to add free photocatalysts or ferrous ion catalysts to the polishing solution, which simplifies the composition of the polishing solution, reduces precipitation formation, and reduces the difficulty of polishing solution preparation and subsequent treatment. Attached Figure Description

[0037] Figure 1 This is a continuous polishing time-material removal rate curve for Example 3 and Comparative Example 5 of the present invention. Detailed Implementation

[0038] The embodiments of the present invention will now be described in detail with reference to the accompanying drawings.

[0039] This invention provides a photocatalytic Fenton-synergistic silicon carbide electrochemical mechanical polishing pad. The polishing pad includes a plastic sheet and a polyurethane porous layer adhered to the plastic sheet. The polyurethane porous layer has a porous damping cloth structure and includes a polymer matrix composed of polyurethane resin containing chelating groups, a photocatalyst, ferrous ion chelates, and composite magnetic particles. The photocatalyst is dispersed in the polymer matrix or loaded on the pore walls of the polymer matrix. Ferrous ions are fixed on the pore walls of the polymer matrix through chelation and form ferrous ion chelates. The composite magnetic particles are dispersed in the polymer matrix.

[0040] The photocatalyst is selected from one or more of TiO2, CeO2-TiO2 heterostructure, Ag@AgCl and g-C3N4, and the particle size of the photocatalyst is 10-100 nm; the chelating agent used to introduce chelating groups can be N-hydroxyethylethylenediaminetriacetic acid, ethylenediaminetetraacetic acid or diethylenetriaminepentaacetic acid; the composite magnetic particles can be CIP@Fe3O4 composite magnetic particles or Fe3O4@SiO2 composite magnetic particles.

[0041] Among them, the CIP@Fe3O4 composite magnetic particles are core-shell structured particles with carbonyl iron powder as the core and iron(III) oxide as the shell. The nano-sized Fe3O4 on its surface has a large specific surface area and catalytic activity, which can serve as an auxiliary catalytic component for the Fenton reaction and give the polishing pad magnetic responsiveness. When an external magnetic field is applied during the polishing process, the modulus and hardness of the polishing pad can be adjusted by regulating the magnetic field strength.

[0042] The photocatalyst nanoparticles are uniformly dispersed on the pore wall surface of the polymer matrix and spatially adjacent to the ferrous ion chelates fixed on the pore walls. This allows the photogenerated electrons produced by the photocatalyst to act on the Fe formed by the Fenton reaction within a shorter transport path. 3+ .

[0043] In this invention, N,N-dimethylformamide is abbreviated as DMF, diphenylmethane-4,4′-diisocyanate is abbreviated as MDI, and material removal rate is abbreviated as MRR.

[0044] The photocatalytic Fenton-synergistic silicon carbide electrochemical mechanical polishing pad of the present invention can be prepared according to the following steps.

[0045] S1, to prepare a polyurethane resin containing a photocatalyst and a chelating agent; The raw materials for preparing polyurethane resin, by mass percentage, include 0.5%–3% 1,4-butanediol, 20%–30% polybutylene adipate diol, 0.5%–5% N-hydroxyethyl ethylenediamine triacetic acid, 5%–15% MDI, 60%–74% DMF, 5%–15% organosilicon prepolymer, 1%–10% photocatalyst nanoparticles, and 5%–20% CIP@Fe3O4 composite magnetic particles. The number average molecular weight of polybutylene adipate diol is 1800–3000.

[0046] 1,4-Butanediol, polybutylene adipate diol, and a portion of DMF were mixed and stirred, and the temperature was raised to 75–85°C. MDI and a portion of DMF were added to carry out the polymerization reaction. Organosilicon prepolymer was added to the reaction system as a reaction raw material. As the viscosity of the reaction system increased, the remaining DMF was added to reduce the viscosity. After reacting for 3–7 hours, the reaction system was cooled to 50–60°C.

[0047] N-hydroxyethyl ethylenediamine triacetic acid, photocatalyst nanoparticles, and CIP@Fe3O4 composite magnetic particles were dispersed in DMF and ultrasonically dispersed for 30–60 min to ensure uniform dispersion of each component. The resulting dispersion was then slowly added to the reaction system, and the reaction was continued for 2–5 h. The temperature was then lowered to 30–40 °C to obtain an organosilicon-modified solvent-based polyurethane resin containing chelating agents, photocatalysts, and composite magnetic particles.

[0048] S2, prepare a porous polyurethane layer; The silicone-modified solvent-based polyurethane resin obtained in step S1 is mixed with DMF at a mass ratio of 60-70:30-40 to prepare a coating slurry. The coating slurry is applied to a plastic substrate and then immersed in a coagulation bath prepared with DMF and pure water at a mass ratio of 10-30:70-90 to allow the coating slurry to solidify and form a polyurethane porous layer. After solidification, the polyurethane porous layer is washed with pure water and dried.

[0049] S3, which fixes ferrous ions; The polyurethane porous layer obtained in step S2 is immersed in a ferrous salt aqueous solution with a mass concentration of 0.1% to 10%, so that the chelating agent in the polyurethane resin reacts with the ferrous ions to form ferrous ion chelates; after immersion, it is dried to obtain a catalytic polyurethane porous layer containing photocatalyst, composite magnetic particles and ferrous ion chelates.

[0050] Ferrous salts can be ferrous sulfate, ferrous chloride, or ferrous nitrate.

[0051] S4, post-processing; The catalytic polyurethane porous layer obtained in step S3 is bonded to a plastic sheet, and then polished and cut to obtain a photocatalytic Fenton synergistic silicon carbide electrochemical mechanical polishing pad.

[0052] When polishing silicon carbide wafers using a polishing pad, the polishing pad is attached to the polishing disc of the electrochemical mechanical polishing equipment. A polishing solution containing 3–7.5 wt% H2O2 and an electrolyte is prepared. The electrolyte can be NaCl or NaNO3. The SiC wafer is connected to the positive terminal of the power supply as the anode, and the polishing disc is connected to the negative terminal of the power supply as the cathode.

[0053] During the polishing process, a wavelength of 365 nm and a light intensity of 50–100 mW / cm² are used. 2 The surface of the polishing pad is irradiated with ultraviolet light, an external voltage of 5–25 V and an external magnetic field of 0–500 mT are applied, the polishing pressure is 15–50 kPa, and the polishing disc speed is 40–80 rpm.

[0054] When a photocatalyst is irradiated with ultraviolet light, taking TiO2 as an example, TiO2 absorbs light energy and generates photogenerated holes and photogenerated electrons. The reaction process is as follows: TiO2+hv→h + +e - ; h + +H2O→·OH+H + ; H + +OH - →·OH.

[0055] Ferric ion chelates fixed on the pore walls of the polymer matrix slowly release Fe in a slightly acidic polishing solution environment. 2+ The released Fe 2+ The hydroxyl radical is generated by the Fenton reaction with H2O2 in the polishing solution. The reaction process is as follows: Fe 2+ +H2O2→Fe 3+ +·OH+OH - .

[0056] Fe formed by the Fenton reaction 3+ After accepting photogenerated electrons from the photocatalyst, it is reduced to Fe. 2+ The reaction process is as follows: e - +Fe 3+ →Fe 2+ .

[0057] Since the photocatalyst and the ferrous ion chelate are co-located near the pore walls of the polymer matrix, the photogenerated electrons can be transferred to the Fe ions over a short distance after generation. 3+ Promote Fe 2+ Regeneration, accelerating Fe 3+ / Fe 2+ The cycle allows the Fenton reaction to continue.

[0058] Under the influence of an external magnetic field, the CIP@Fe3O4 composite magnetic particles enable the polishing pad to exhibit magnetic response characteristics. By adjusting the magnetic field strength, the modulus and hardness of the polishing pad can be adjusted, thereby changing the contact state and polishing pressure between the polishing pad and the SiC wafer.

[0059] Under the influence of an applied electric field, the surface of the SiC wafer, which serves as the anode, undergoes anodic oxidation to form a SiO2 oxide layer. The reaction process is as follows: SiC + 4H₂O + 8h + →SiO2+CO2+8H + .

[0060] The formed SiO2 oxide layer has a lower hardness than the SiC substrate and is then removed by mechanical friction from a polishing pad and abrasive. Photocatalytic reactions, Fenton reactions, and photogenerated electrons promote Fe... 3+ Reduction, magnetic response modulation, electrochemical anodizing, and mechanical removal are performed on the same polishing interface, enabling a continuous process of oxidation, removal, and re-oxidation on the SiC wafer surface.

[0061] Example 1 This embodiment provides a photocatalytic Fenton-synergistic silicon carbide electrochemical mechanical polishing pad containing TiO2 photocatalyst, CIP@Fe3O4 composite magnetic particles and divalent iron ion chelates.

[0062] 0.65 kg of 1,4-butanediol, 8.50 kg of polybutylene adipate diol, and 5 kg of DMF were added to a reactor, wherein the number average molecular weight of polybutylene adipate diol was 2000. The reactor was heated to 80°C, and 3.17 kg of MDI and 5 kg of DMF were added to carry out the polymerization reaction, with the reaction temperature controlled at 75–85°C. As the viscosity of the reaction system increased, 15.84 kg of DMF was added to adjust the viscosity of the system. After the reaction continued for 5 hours, the temperature of the material in the reactor was reduced to 50°C.

[0063] 0.29 kg of N-hydroxyethyl ethylenediamine triacetic acid, 0.5 kg of nano-TiO2, and 1.0 kg of CIP@Fe3O4 composite magnetic particles were dispersed in 3 kg of DMF. The nano-TiO2 was P25 type TiO2 with an average particle size of 21 nm, and the CIP@Fe3O4 composite magnetic particles had an average particle size of 5 μm. The resulting dispersion was added dropwise to a reaction vessel, and the reaction was continued for 3 h. The temperature was then lowered to 35 °C to obtain a solvent-based polyurethane resin containing TiO2, N-hydroxyethyl ethylenediamine triacetic acid, and CIP@Fe3O4 composite magnetic particles.

[0064] 65 kg of the obtained polyurethane resin and 35 kg of DMF were added to a mixing tank and stirred evenly. Vacuum degassing was then performed to obtain a coating slurry. The coating slurry was coated onto a PET plastic sheet with a coating thickness of 1.8 mm. The sheet was then immersed in a coagulation bath prepared with DMF and pure water at a mass ratio of 15:85 for coagulation to obtain a polyurethane porous layer. After coagulation, the polyurethane porous layer was washed with pure water and dried.

[0065] The dried polyurethane porous layer was immersed in a 2% FeSO4 aqueous solution for 2 hours to allow the N-hydroxyethyl ethylenediamine triacetic acid in the polyurethane resin to react with the FeSO4. 2+ A chelation reaction occurs; after soaking, the material is dried, and then the resulting catalytic polyurethane porous layer is pasted onto a plastic sheet. After grinding and cutting, a polishing pad containing TiO2 photocatalyst, CIP@Fe3O4 composite magnetic particles, and divalent iron ion chelates is obtained.

[0066] The obtained polishing pad was attached to the polishing disk of the ECMP equipment, and a polishing solution containing 5 wt% H2O2 and 0.6 mol / L NaCl was prepared. The Si surface of the 4H-SiC wafer was used as the surface to be polished, and the SiC wafer was used as the anode, with an applied voltage of 10 V. During the polishing process, a wavelength of 365 nm and a light intensity of 80 mW / cm² were used. 2 The surface of the polishing pad was irradiated with ultraviolet light, an external magnetic field of 200 mT was applied, the polishing pressure was 25 kPa, the polishing disc rotation speed was 60 rpm, and the polishing time was 2 h.

[0067] According to the test, the material removal rate (MRR) of this embodiment is about 3.5 μm / h, and the surface roughness Ra of the SiC wafer after polishing is about 0.25 nm.

[0068] Example 2 This embodiment is basically the same as Example 1, except that a CeO2-TiO2 heterostructure composite photocatalyst is used instead of nano-TiO2 in Example 1. The CeO2-TiO2 heterostructure composite photocatalyst is prepared by hydrothermal method, the molar ratio of Ce to Ti is 1:10, and the amount added is 0.8 kg.

[0069] The remaining polishing pad preparation steps and polishing conditions are the same as in Example 1.

[0070] According to the test, the material removal rate (MRR) of this embodiment is about 4.0 μm / h, and the surface roughness Ra of the SiC wafer after polishing is about 0.20 nm.

[0071] Example 3 This embodiment is basically the same as Example 1, except that the nano-TiO2 in Example 1 is replaced by Ag@AgCl plasma photocatalyst. The Ag@AgCl plasma photocatalyst is prepared by precipitation-chemical reduction method and the amount added is 0.3 kg.

[0072] The remaining polishing pad preparation steps and polishing conditions are the same as in Example 1.

[0073] According to the test, the material removal rate (MRR) of this embodiment is about 4.2 μm / h, and the surface roughness Ra of the SiC wafer after polishing is about 0.18 nm.

[0074] Comparative Example 1 This comparative example is basically the same as Example 1, except that no photocatalyst is added when preparing the polyurethane resin. The resulting polishing pad contains N-hydroxyethyl ethylenediamine triacetic acid, ferrous ion chelate and CIP@Fe3O4 composite magnetic particles, but does not contain a photocatalyst; and ultraviolet light is not turned on during the polishing process.

[0075] The material removal rate (MRR) of this comparative example was approximately 1.8 μm / h, and the surface roughness (Ra) of the SiC wafer after polishing was approximately 0.55 nm.

[0076] Comparative Example 2 This comparative example is basically the same as Example 1, except that CIP@Fe3O4 composite magnetic particles are not added when preparing the polyurethane resin. The resulting polishing pad contains a photocatalyst, N-hydroxyethylethylenediaminetriacetic acid and ferrous ion chelate, but does not contain CIP@Fe3O4 composite magnetic particles; no external magnetic field is applied during the polishing process.

[0077] The material removal rate (MRR) of this comparative example was approximately 2.8 μm / h, and the surface roughness (Ra) of the SiC wafer after polishing was approximately 0.35 nm.

[0078] Comparative Example 3 This comparative example is basically the same as Example 1, except that a photocatalyst is added when preparing the polyurethane resin, but N-hydroxyethylethylenediaminetriacetic acid is not added, and Fe is not added to the polishing solution. 2+ .

[0079] The material removal rate (MRR) of this comparative example was approximately 1.0 μm / h, and the surface roughness (Ra) of the SiC wafer after polishing was approximately 0.50 nm.

[0080] Comparative Example 4 This comparative example uses the polishing pad prepared in Example 1. The difference is that no external voltage is applied during the polishing process, that is, no electrochemical mechanical polishing is performed, only photocatalytic Fenton synergistic chemimechanical polishing is performed, and the other polishing conditions are the same as in Example 1.

[0081] The material removal rate (MRR) of this comparative example was approximately 1.0 μm / h, and the surface roughness (Ra) of the SiC wafer after polishing was approximately 0.40 nm.

[0082] Comparative Example 5 This comparative example is basically the same as Example 1, except that no photocatalyst, CIP@Fe3O4 composite magnetic particles, or N-hydroxyethyl ethylenediamine triacetic acid are added when preparing the polyurethane resin. The resulting polishing pad does not contain photocatalyst, composite magnetic particles, or ferrous ion chelates. No ultraviolet light is turned on or an external magnetic field is applied during the polishing process.

[0083] The material removal rate (MRR) of this comparative example was approximately 0.35 μm / h, and the surface roughness (Ra) of the SiC wafer after polishing was approximately 0.82 nm.

[0084] The polishing results of Examples 1-3 and Comparative Examples 1-5 are shown in Table 1.

[0085] Table 1 Polishing results of different polishing pads

[0086] As shown in Table 1, the MRR of Examples 1 to 3 was 3.5 to 4.2 μm / h and the surface roughness Ra was 0.18 to 0.25 nm, which were all better than the comparative examples without the simultaneous addition of photocatalyst, ferrous ion chelate and CIP@Fe3O4 composite magnetic particles.

[0087] Compared with Comparative Example 1, after setting a photocatalyst and turning on ultraviolet light, Examples 1-3 showed a significant increase in MRR and a decrease in surface roughness, indicating that photocatalysis can improve the oxidation and removal efficiency of SiC surface. Compared with Comparative Example 2, after CIP@Fe3O4 composite magnetic particles were set and an external magnetic field was applied in Examples 1-3, the material removal rate and surface quality were further improved. Compared to Comparative Example 3, N-hydroxyethylethylenediaminetriacetic acid was prepared and Fe was... 2+ After chelation fixation, the MRR of the polishing pad was significantly improved; compared with Comparative Example 4, electrochemical anodizing can improve the oxidation and removal efficiency of SiC surface after applying an external voltage. The polishing pad used in Comparative Example 5 does not contain photocatalysts, composite magnetic particles, or ferrous ion chelates, and has the lowest MRR and the highest surface roughness.

[0088] Test Example 1 Fe in polishing pads was determined using the o-phenanthroline spectrophotometric method. 2+ The fixed amount and release behavior.

[0089] Take 1.0 g of polishing pad samples prepared in Example 1 and Comparative Example 3 respectively. The polishing pad in Example 1 contains N-hydroxyethyl ethylenediamine triacetic acid, while the polishing pad in Comparative Example 3 does not contain N-hydroxyethyl ethylenediamine triacetic acid. The Fe content in the two groups of polishing pad samples was measured respectively. 2+ A fixed amount was then placed in 100 mL of citric acid buffer solution at pH 3.5, and the mixture was magnetically stirred at 25 °C. The released solution was collected every 30 min to determine the Fe content. 2+ Concentration, examining Fe 2+ How the cumulative release changes over time.

[0090] Each sample was tested three times, i.e., n=3. The test data are expressed as mean ± standard deviation. The test results are shown in Table 2.

[0091] Table 2 Fe 2+ Results of fixed amount and cumulative release test

[0092] As shown in Table 2, Fe in Example 1 2+ The fixed amount was 8.52 mg / g, significantly higher than the 0.93 mg / g of Comparative Example 3; Fe in Example 1 2+ It maintained a slow, continuous release over 240 minutes, while Fe in Comparative Example 3... 2+ It is released rapidly and reaches equilibrium within the first 60 minutes.

[0093] The above results indicate that N-hydroxyethylethylenediaminetriacetic acid can increase Fe 2+ The amount of Fe fixed in the polyurethane porous layer, and made Fe 2+ The change from rapid release over a short period to slow, sustained release over a longer period indicates that the chelating agent can achieve Fe 2+ Stable fixation and continuous release within the polishing pad.

[0094] Test Example 2 Polishing pads prepared in Example 3 and Comparative Example 5 were used to conduct continuous polishing tests for 40 hours under the same polishing conditions. The material removal rate (MRR) was measured every 2 hours during the polishing process. A curve showing the relationship between polishing time and MRR was plotted based on the test results. The test results are as follows: Figure 1 As shown.

[0095] Depend on Figure 1It can be seen that the polishing pad prepared in Example 3 maintained an MRR of 3.90 to 4.30 μm / h during a continuous 40-hour polishing process. The test curve showed only slight fluctuations and did not show a trend of continuous decline with the extension of polishing time. This indicates that the polishing pad prepared in Example 3 can maintain a relatively stable material removal capacity during long-term continuous use.

[0096] The polishing pad prepared in Comparative Example 5 had an MRR of approximately 0.30 μm / h in the initial stage of continuous polishing, which gradually decreased with the extension of polishing time and approached 0 in the later stage of continuous polishing. This indicates that without the addition of photocatalyst, CIP@Fe3O4 composite magnetic particles and ferrous ion chelates, the material removal capacity of the polishing pad is low and there is a significant attenuation during continuous polishing.

[0097] In Example 3, Ag@AgCl photocatalyst, ferrous ion chelate, and CIP@Fe3O4 composite magnetic particles were co-located in a polyurethane porous layer. Upon excitation by ultraviolet light, the photocatalyst generated photogenerated electrons and holes. These photogenerated electrons promoted the formation of Fe during the Fenton reaction. 3+ Reduced to Fe 2+ Chelating agents, on the other hand, cause Fe... 2+ Maintaining stable fixation and continuous release within the polishing pad is beneficial for preserving Fe. 3+ / Fe 2+ Cycle and the continuous generation of hydroxyl radicals.

[0098] Therefore, Example 3 was able to maintain a high and relatively stable MRR during a continuous 40-hour polishing process, indicating that the co-positioning of the photocatalyst, ferrous ion chelate, and composite magnetic particles in the polishing pad can improve the material removal stability of the polishing pad during long-term continuous polishing.

[0099] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any person skilled in the art can easily conceive of various variations or substitutions within the technical scope disclosed in the present invention, and these should all be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.

Claims

1. A photocatalytic Fenton-synergistic silicon carbide electrochemical mechanical polishing pad, characterized in that, The polishing pad includes a plastic sheet and a porous polyurethane layer adhered to the plastic sheet. The porous polyurethane layer is a porous damping cloth structure, comprising a polymer matrix composed of polyurethane resin containing chelating groups, a photocatalyst, ferrous ion chelates, and composite magnetic particles. The photocatalyst is dispersed in the polymer matrix or loaded on the pore walls of the polymer matrix. Ferrous ions are fixed on the pore walls of the polymer matrix through chelation and form ferrous ion chelates. The composite magnetic particles are dispersed in the polymer matrix.

2. The photocatalytic Fenton-synergistic silicon carbide electrochemical mechanical polishing pad according to claim 1, characterized in that, The photocatalyst is selected from one or more of TiO2, CeO2-TiO2 heterostructure, Ag@AgCl and g-C3N4, and the particle size of the photocatalyst is 10-100 nm.

3. The photocatalytic Fenton-synergistic silicon carbide electrochemical mechanical polishing pad according to claim 1, characterized in that, The chelating group is introduced by a chelating agent selected from one or more of N-hydroxyethylethylenediaminetriacetic acid, ethylenediaminetetraacetic acid, and diethylenetriaminepentaacetic acid.

4. The photocatalytic Fenton-synergistic silicon carbide electrochemical mechanical polishing pad according to claim 1, characterized in that, The composite magnetic particles are CIP@Fe3O4 composite magnetic particles or Fe3O4@SiO2 composite magnetic particles. The CIP@Fe3O4 composite magnetic particles are core-shell structure particles with carbonyl iron powder as the core and iron(III) oxide as the shell.

5. The photocatalytic Fenton-synergistic silicon carbide electrochemical mechanical polishing pad according to claim 1, characterized in that, The photocatalyst is a photocatalyst nanoparticle uniformly dispersed on the surface of the pore wall of the polymer matrix, and the photocatalyst nanoparticle and the divalent iron ion chelate fixed on the pore wall are spatially adjacent.

6. A method for preparing a photocatalytic Fenton-synergistic silicon carbide electrochemical mechanical polishing pad according to any one of claims 1 to 5, characterized in that, Includes the following steps: S1, 1,4-Butanediol, polybutylene adipate diol, N-hydroxyethyl ethylenediamine triacetic acid, diphenylmethane-4,4′-diisocyanate, organosilicon prepolymer, photocatalyst nanoparticles and CIP@Fe3O4 composite magnetic particles are mixed and reacted in N,N-dimethylformamide to obtain an organosilicon-modified solvent-based polyurethane resin containing chelating agent, photocatalyst and composite magnetic particles; S2, the silicone-modified solvent-based polyurethane resin obtained in step S1 is mixed with N,N-dimethylformamide to prepare a coating slurry, the coating slurry is coated on a plastic substrate and then immersed in a coagulation bath prepared with N,N-dimethylformamide and pure water to solidify, thereby obtaining a polyurethane porous layer, and the polyurethane porous layer is washed with pure water and dried. S3, the polyurethane porous layer obtained in step S2 is immersed in a ferrous salt aqueous solution, so that the chelating agent in the polyurethane resin reacts with the ferrous ions to form a ferrous ion chelate. After drying, a catalytic polyurethane porous layer containing a photocatalyst, composite magnetic particles and ferrous ion chelate is obtained. S4, the catalytic polyurethane porous layer is bonded to the plastic sheet, and then polished and cut to obtain the photocatalytic Fenton synergistic silicon carbide electrochemical mechanical polishing pad.

7. The preparation method according to claim 6, characterized in that, In step S1, by mass percentage, the 1,4-butanediol is 0.5%–3%, the polybutylene adipate diol is 20%–30%, the N-hydroxyethyl ethylenediamine triacetic acid is 0.5%–5%, the diphenylmethane-4,4′-diisocyanate is 5%–15%, the N,N-dimethylformamide is 60%–74%, the organosilicon prepolymer is 5%–15%, the photocatalyst nanoparticles are 1%–10%, the CIP@Fe3O4 composite magnetic particles are 5%–20%, and the number average molecular weight of the polybutylene adipate diol is 1800–3000.

8. The preparation method according to claim 6, characterized in that, In step S1, the 1,4-butanediol, polybutylene adipate diol, and a portion of N,N-dimethylformamide are mixed and stirred, and the temperature is raised to 75-85°C. The diphenylmethane-4,4′-diisocyanate and a portion of N,N-dimethylformamide are added to carry out a polymerization reaction. As the viscosity of the reaction system increases, the remaining N,N-dimethylformamide is added. After reacting for 3-7 hours, the temperature is lowered to 50-60°C. The N-hydroxyethyl ethylenediamine triacetic acid, photocatalyst nanoparticles, and CIP@Fe3O4 composite magnetic particles are dispersed in N,N-dimethylformamide and ultrasonically dispersed for 30-60 minutes before being added to the reaction system. The reaction continues for 2-5 hours, and the temperature is lowered to 30-40°C.

9. The preparation method according to claim 6, characterized in that, In step S2, the mass ratio of the organosilicon-modified solvent-based polyurethane resin to N,N-dimethylformamide is 60-70:30-40, and the mass ratio of N,N-dimethylformamide to pure water in the coagulation bath is 10-30:70-90.

10. The preparation method according to claim 6, characterized in that, In step S3, the mass concentration of the ferrous salt aqueous solution is 0.1% to 10%, and the ferrous salt is selected from one or more of ferrous sulfate, ferrous chloride, and ferrous nitrate.

Citation Information

Patent Citations

  • Silicon carbide chemical mechanical polishing solution based on photocatalytic mechanism

    CN115386298A

  • A method of photoelectrocatalytic enhanced fixed abrasive polishing of monocrystalline silicon carbide

    CN116214359B